Molecular Characterisation and Genetic Diversity Analysis through SSR Markers in Germplasm Lines of Green gram [Vigna radiata (L.) Wilczek] - M. S. P., Kanavi; Rangaiah, S.; B. T, Krishnaprasad (International Journal of Bio-resource and Stress Management, 2019)
Fifty-six germplasm lines of Green gram [Vigna radiata (L.) Wilczek] were used to determine the extent of genetic diversity through simple sequence repeats (SSR) markers. Molecular characterization of 56 green gram genotypes was done with fifteen standardized SSR primers. All primers showed scorable polymorphism. DNA bands generated from SSR-PCR amplification were scored using binary system and the information was used to calculate Jackard’s similarity matrix using NTSYS-pc version 2.1 The genetic similarity between genotypes ranged from 0.35 to 1.00. A minimum similarity coefficient of 0.35 was observed between genotypes LGG-585 and LGG-573 and maximum was between KKM-3 and TM-962 (1.00). The average genetic similarity value of 0.85 that existed among the germplasm lines indicate moderate level of genetic diversity within the self-pollinated crop green gram, which is possibly due to accumulation of novel gene combinations in response to dynamic pressures of natural selection. The UPGMA dendrogram based on SSR results divided the 56 green gram genotypes into eight main clusters under which the cluster I was highly diverse compared to all other clusters and consisted of 15 genotypes, followed by cluster II with 9 genotypes, cluster VI with 7 genotypes, cluster IV and V with 6 genotypes, cluster III with 5 genotypes, and cluster VII and VIII with 4 genotypes each. The present study revealed that SSR markers may be successfully utilized for determining genetic diversity and relationships among germplasm lines of green gram.